Mengurai Identitas dalam Konteks Regionalisme Kawasan Afrika: Perjuangan Melawan Apartheid Menuju Persatuan yang Solid - Ayu, Galuh Anissa Sekar (Global and Policy Journal of International Relations, 2023)
Penelitian ini bertujuan untuk menganalisis regionalisme di Kawasan Afrika dalam dimensi sosial budaya. Melalui eksplorasi tersebut, penulis akan menjelaskan proses integrasi kawasan melalui penjabaran regionalisme, analisis latar belakang praktik Apartheid, hubungan antara regionalisme, norma, dan identitas, serta manifestasi gerakan pan-Afrikanisme melalui institusi regional Organization of African Unity dan African Union. Sebagai alat analisis, penulis menggunakan pendekatan regionalisme baru (new regionalism approach/NRA) dengan metode penelitian deskriptif kualitatif. Hasil penelitian menunjukkan identitas, norma, nilai, dan prinsip berperan sebagai intangible forces, sedangkan praktik politik dan eksploitasi sebagai tangible forces dalam proses regionalisme di Kawasan Afrika. Regionalisme yang terjadi di Kawasan Afrika berdasarkan aspek sosial disebabkan oleh faktor internal (dinamika kawasan akibat praktik kolonialisme dan Apartheid) maupun eksternal (nilai dan norma universal yang dibawa oleh arus globalisasi). Melalui pendekatan regionalisme baru, diperoleh peran aktor non-negara yang turut mewarnai regionalisme kawasan. Terakhir, panggung politik global yang dinamis juga menuntut OAU untuk merubah haluan di tengah gempuran zaman.Kata kunci: regionalisme; apartheid; new regionalism approach;  Afrika; sosial budayaAbstract This research aims to analyze regionalism in the African Region in the dimension of socio-cultural aspects. Through this exploration, the author will explain the regional integration process by elaborating on regionalism, analyzing the background of Apartheid practices, the relationship between regionalism, norms, and identity, as well as the manifestations of the Pan-African movement through the regional institutions of the Organization of African Unity and the African Union. As an analytical tool, the author employs the New Regionalism Approach (NRA) with a qualitative descriptive research method. The research findings indicate that identity, norms, values, and principles play a role as intangible forces, while political practices and exploitation act as tangible forces in the process of regionalism in the African Region. Regionalism in the African Region, based on social aspects, is influenced by both internal factors (regional dynamics resulting from colonialism and Apartheid practices) and external factors (universal values and norms brought by the tide of globalization). Through the new regionalism approach, the role of non-state actors shaping regionalism in the region is evident. Finally, the dynamic global political stage also demands a shift in direction for the OAU amid the challenges of the times.Keywords: regionalism; apartheid; new regionalism approach; Africa; socio-culturalDOI: https://doi.org/10.33005/jgp.v11i02.4095